PERSEPSI MASYARAKAT TERHADAP PENGGUNAAN CADAR DI KALANGAN MAHASISWI - Indo Santalia; Guruh Ryan Aulia; Rafika Syahdina; Nur Qalby; Muh. Raihan Gymnastiar Muin (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This research aimed to empirically examine public perceptions toward the use of niqab among female students at Islamic higher education institutions, as well as to explore the social responses, stigma, and coping strategies experienced by niqab-wearing students. The study focused on identifying the motivations underlying the decision to wear the niqab, community attitudes toward this practice, and its psychological and social implications. This research employed a qualitative descriptive approach, with data collected through in-depth interviews and observations involving female students who wear niqab at the State Islamic Higher Education Institution (PTKIN) in Parepare City, South Sulawesi. The informants were selected using purposive sampling techniques. Data were analyzed inductively by organizing the findings into thematic categories related to motivation, social perception, stigma, and individual responses. The results indicate that the decision to wear the niqab is influenced by various factors, including religious commitment, personal comfort, environmental influence, religious understanding, and personal life experiences. Community responses toward niqab-wearing students vary, ranging from acceptance and neutrality to negative stigma and discrimination, which are often associated with assumptions of radicalism, social exclusivity, and perceived limitations in social and professional life. Despite these challenges, the female students demonstrated adaptive coping strategies, such as maintaining positive attitudes, strengthening religious commitment, engaging in social interactions, and exemplifying moral conduct as efforts to counter negative perceptions and gradually build social acceptance.